Assessing policy-makers', academics' and experts' satisfaction with the performance of the Palestinian health research system: a qualitative study - Mohammed AlKhaldi; Yehia Abed; Constanze Pfeiffer; Saleem Haj-Yahia; Abdulsalam Alkaiyat; Marcel Tanner (BMC, 2018)
Abstract Background There is a growing demand within international health agencies to ensure health research systems (HRSs) are strengthened and well-functioning to support healthcare systems (HCSs). Understanding HRS performance through system actors is an indispensable move in analysing this system. This study aims to examine policy-makers', academics' and experts' satisfaction with overall HRS performance, while also investigating their perceptions about political will and attention towards health research. Ultimately, we want to identify gaps related to performance and generate insights on how to move forward for HRS performance strengthening. Methods This study was carried out in Palestine, targeting three sectors, namely government institutions, public health universities, and major local and international health non-governmental organisations (NGOs). Semi-structured, in-depth interviews (IDIs) and focus group discussions (FGDs) were conducted with participants. The institutions from the three sectors were selected based on stated criteria and peer reviews. Data were translated from Arabic into English, transcribed, content checked by the principal investigator, imported to a software programme (MAXQDA 12), and then coded. Thematic content analysis was used. Results A total of 104 experts participated in 52 IDIs and 52 experts participated in 6 FGDs. Findings revealed three principal domains. First, the HRS in Palestine is remarkably underperforming, and the majority of experts were unsatisfied. Participants perceived the system as ineffective and inefficient, poorly managed and lacking systematic assessment. Second, the factors behind system underperformance were (1) an unstructured system and the lack of a research culture as well as of a governing body or policies; (2) health research was seen as individualistic, non-development driven and unutilised in policy decisions; and (3) considerably deficient coordination and essential resources. The third finding showed inadequate political support and engagement, which then also related to system underperformance. Conclusions The Palestinian HRS is perceived as underperforming by health experts at different levels, where research is not on the leadership agendas. Potential actions should be taken to actively engage the state health decision-makers and inform them of the importance, uses and impacts of performance assessment. Findings urge policy-makers and legislators to build an inclusive and national body of governance with agreed strategies including fundamentally hybrid and aligned performance assessment mechanisms, such as a research observatory platform. In addition, it is recommended to establish a strategic plan to expand professionals' research awareness and abilities, as well as empower the institution's research monitoring and evaluation capacities.